2009
DOI: 10.1002/jbt.20300
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of diepoxybutane‐induced p53 regulation in human cells

Abstract: Diepoxybutane (DEB) is the most potent active metabolite of the environmental chemical 1,3-butadiene (BD). BD is a known mutagen and human carcinogen and possesses multisystems organ toxicity. We previously reported the elevation of p53 in human TK6 lymphoblasts undergoing DEB-induced apoptosis. In this study, we have characterized the DEB-induced p53 accumulation and investigated the mechanisms by which DEB regulates this p53 accumulation. The elevation of p53 levels in DEB-exposed TK6 lymphoblasts and human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…ATM is recognized as an important regulator of p53 checkpoint function, as ATM-deficient cells fail to induce or stabilize p53 protein levels in response to some types of DNA damage, such as ionizing radiation. This may be particularly relevant to environmental carcinogens, as transforming growth factor-beta ATM-deficient lymphoblasts exposed to the chemical diepoxybutane are unable to stabilize p53 protein levels to the same extent as cells with wild-type ATM (15). Thus, although many p53-independent functions exist for ATM, disruption of p53 growth-inhibitory checkpoint function is a major mechanism by which ATM-deficient cancer cells fail to respond to DNAdamaging agents, including specific environmental pollutants.…”
Section: P53mentioning
confidence: 99%
“…ATM is recognized as an important regulator of p53 checkpoint function, as ATM-deficient cells fail to induce or stabilize p53 protein levels in response to some types of DNA damage, such as ionizing radiation. This may be particularly relevant to environmental carcinogens, as transforming growth factor-beta ATM-deficient lymphoblasts exposed to the chemical diepoxybutane are unable to stabilize p53 protein levels to the same extent as cells with wild-type ATM (15). Thus, although many p53-independent functions exist for ATM, disruption of p53 growth-inhibitory checkpoint function is a major mechanism by which ATM-deficient cancer cells fail to respond to DNAdamaging agents, including specific environmental pollutants.…”
Section: P53mentioning
confidence: 99%
“…Accordingly, Vijayakumaran et al (2015) showed that dysfunction of p53 occurs in half the cases of cancers by direct mutations in the gene, whereas in the remainder, p53 becomes dysfunctional through a variety of regulatory mechanisms. For example, p53 protein stability is regulated by specific kinase pathways, including the Ataxia-Telangiectasia-mutated (ATM)-checkpoint kinase 2 (Chk2) pathway, as ATM-deficient cells fail to induce or stabilize p53 protein levels in response to some types of DNA damage, such as ionizing radiation and some environmental carcinogens (Yadavilli et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This was performed essentially as previously described. 17,40 Cells were placed in fresh media 24 h prior to each experiment. Cells were then washed and seeded in fresh media at a density of 2.0 × 10 5 cells/mL, prior to the addition of 10-µM DEB or vehicle for 24 and 48 h. All DEB dilutions were performed in RPMI.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analysis was utilized to determine the levels of activated phospho-ERK1/2(Thr202/Tyr204), activated phospho-MEK1/2(ser217/221), phospho-p53 (serine-15), total ERK1/2, p53, and GAPDH in all extracts. The procedure was performed as previously described, 17,40 and as modified for fluorescent antibody imaging on the Li-Cor Odyssey system (Li-Cor, Inc., Lincoln, NE), according to the system manufacturer’s instructions. Briefly, experimental and control cells were harvested and lysed by gentle vortexing at 4°C in TBSTDS (10-mM tris, (pH 7.5), 150-mM sodium chloride, 1-mM EDTA, 1% triton X-100, 0.5% sodium deoxycholate, 0.5% sodium-dodecyl-sulfate (SDS), 0.02% sodium azide, and 0.0004% sodium fluoride) supplemented with protease inhibitors (1-mM phenylmethylsufonyl fluoride, 2-μg/mL aprotinin, and 0.1-mM leupeptin) and a phosphatase inhibitor cocktail (2.5-mM sodium pyrophosphate, 1-mM sodium orthovanadate, 25-mM sodium fluoride, and 2-mM β-glycerol-phosphate).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation